The role of the police of the Republic of Indonesia in managing cross-border crimes of West Kalimantan Indonesia - Sy. Hasyim Azizurrahman; Elyta Elyta; Syarif Redha Fachmi Al Qadrie (Journal of Research in Social Science and Humanities, 2024)
Study this done by memorable for describe effort countermeasures crime cross limit with Sarawak through the investigation by the Resort Police in the border area of West Kalimantan and for view and analyze development investigators. Method approach used this study by qualitative approach that results from analysis qualitative. Following title the research will be conducted at the Police West Kalimantan and Sarawak border. That is Police Sambas Resort and the Indonesian National Police, which became the source policy countermeasures crime. Research results are Duties and powers Police specifically Police Resort in the border region of West Kalimantan with Sarawak, do investigation have carried out by regulations legislation for cope crime cross boundaries that occur in the regions of West Kalimantan and Sarawak. Police are looking after security and order Public and organizing and building obedience self member Public to regulation legislation; they need be equipped with adequate facilities and infrastructure.